The use of port state measures as a tool of combating illegal unreported unregulated fishing: Is there a need for expansion of coastal state jurisdiction? - Ogega, Peris B (University of Cape Town, 2021)
This dissertation examines the scope and limitations of port state jurisdiction with respect to the enforcement of international conservation and management measures established under international and national instruments. The current fisheries regulatory regimes rely primarily on flag states to enforce these measures against foreign vessels. The aim of this dissertation is to recommend an expansion of port state enforcement jurisdiction over foreign vessels when fishing in the high seas. The expansion of port state jurisdiction supplements the role of flag states in enforcing the provisions of international conventions and agreements applicable in the high seas and also fills in where flag of convenience fishing vessels have failed to do so. To support this view, the dissertation will compare the issue of illegal unreported unregulated fishing with the issue of marine pollution. The significance of this comparison is to show how provisions in regard to marine pollution, have legitimized the expansion of port state jurisdiction to the extent that port states have enforcement jurisdiction over foreign flagged vessels which violate the provisions of LOSC relating to marine pollution in the high seas.